Mitochondrial Transfer Induced by Adipose-Derived Mesenchymal Stem Cell Transplantation Improves Cardiac Function in Rat Models of Ischemic Cardiomyopathy - Mori, Daisuke; Miyagawa, Shigeru; Kawamura, Takuji; Yoshioka, Daisuke; Hata, Hiroki; Ueno, Takayoshi; Toda, Koichi; Kuratani, Toru; Oota, Miwa; Kawai, Kotoe; Kurata, Hayato; Nishida, Hiroyuki; et al. (Cell Transplantation, 2023)
Although mesenchymal stem cell transplantation has been successful in the treatment of ischemic cardiomyopathy, the underlying mechanisms remain unclear. Herein, we investigated whether mitochondrial transfer could explain the success of cell therapy in ischemic cardiomyopathy. Mitochondrial transfer in co-cultures of human adipose-derived mesenchymal stem cells and rat cardiomyocytes maintained under hypoxic conditions was examined. Functional recovery was monitored in a rat model of myocardial infarction following human adipose-derived mesenchymal stem cell transplantation. We observed mitochondrial transfer in vitro, which required the formation of cell-to-cell contacts and synergistically enhanced energy metabolism. Rat cardiomyocytes exhibited mitochondrial transfer 3 days following human adipose-derived mesenchymal stem cell transplantation to the ischemic heart surface post-myocardial infarction. We detected donor mitochondrial DNA in the recipient myocardium concomitant with a significant improvement in cardiac function. Mitochondrial transfer is vital for successful cell transplantation therapies and improves treatment outcomes in ischemic cardiomyopathy.